2009 IEEE International Solid-State Circuits Conference - Digest of Technical Papers 2009
DOI: 10.1109/isscc.2009.4977376
|View full text |Cite
|
Sign up to set email alerts
|

A remote-powered RFID tag with 10Mb/s UWB uplink and −18.5dBm sensitivity UHF downlink in 0.18µm CMOS

Abstract: A remote-powered UWB RFID tag in 0.18μm CMOS is presented. The innovation is to employ asymmetric communication links, i.e. UWB uplink and UHF downlink in order to achieve extremely low power, high data rate and accurate positioning. Measurement shows the tag can operate up to 10Mb/s with minimum input power of 14.1μW, corresponding to 13.9 meters of operation range.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
43
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(43 citation statements)
references
References 6 publications
0
43
0
Order By: Relevance
“…Fig. 3 plots the change in power consumption of low-power LSI chips reported from 2007 to 2014 at ISSCC and VLSI Circuits [3,4,5,6,7,8,9,10,11,12,13,14,15,16,17,18,19,20,21,22,23,24,25,26,27,28,29,30,31,32,33,34,35,36,37], which are the most popular international conferences in the semiconductor industry. It is found that there are three domains: milliwatt, microwatt, and nanowatt.…”
Section: Trends In Circuit Technology and Energy Harvestingmentioning
confidence: 99%
“…Fig. 3 plots the change in power consumption of low-power LSI chips reported from 2007 to 2014 at ISSCC and VLSI Circuits [3,4,5,6,7,8,9,10,11,12,13,14,15,16,17,18,19,20,21,22,23,24,25,26,27,28,29,30,31,32,33,34,35,36,37], which are the most popular international conferences in the semiconductor industry. It is found that there are three domains: milliwatt, microwatt, and nanowatt.…”
Section: Trends In Circuit Technology and Energy Harvestingmentioning
confidence: 99%
“…4 shows the system architecture of the display tag. The power management unit (PMU) implements a duty-cycled structure based on the design in [18] to improve the system sensitivity when the display is refreshed. Two voltage sensors (Vsen) switch on and off two low-drop-out (LDO) regulators according to the rectified voltage over a storage capacitor.…”
Section: For Display Cells With 10mmmentioning
confidence: 99%
“…In order to power on the core circuit in parallel with display refreshing, a duty-cycled PMU based on the design in [18] is implemented. A Vsen for the 1.8 V LDO activates the display driving only when the rectified voltage in the storage capacitor surpasses a certain value (2.8 V in this system) and stops it when the voltage drops below another value (1.9 V).…”
Section: B Duty-cycled Power Management Unitmentioning
confidence: 99%
“…However, the field from the reader can be modified by the existence of a ground plane and external noises. Thus, it producesa dark area where the intensity of the field is too small to excite the transponders [4][5].…”
Section: Introductionmentioning
confidence: 99%